Demographic and attitudinal legacies of the Armenian genocide - Max Schaub (Post-Soviet Affairs, 2022)
This paper presents the results of the first-ever representative survey on the demographic and attitudinal legacies of the Armenian genocide. The data, collected in 2018, maps the varied geographical origins of the citizens of contemporary Armenia and traces their links to the genocide. Around half of contemporary Armenians descend from refugees of the genocide, while about a third had family members killed. The data also inform debates on how violence transforms societies. Respondents who lost family members during the genocide show elevated levels of ethnocentrism, and lower levels of prosocial behaviour. However, rather than victimization being associated with militarism and hawkishness, the same individuals tend to be less supportive of military solutions. Even though the genocide took place more than a century ago, its demographic and attitudinal legacies remain clearly visible in contemporary Armenia.
Keywords: 330; genocide; violence; legacy; demography; political attitudes; representative survey; Armenia